(untitled) (American Journal of Business Management, Economics and Banking, 2022)
The study aimed to demonstrate the importance of training and scientific qualification and their impact on enhancing the efficiency of the external auditor in auditing fair value estimates and its reflection on the development of professional doubts for the auditor. About the Council of the Auditing and Oversight Profession in Iraq for the year 2022. Among the results of the research, there is a statistical significance for the external auditors in Iraq in having training and technical qualification and having a sufficient understanding of the activity of the economic unit in order to realize their responsibilities in identifying and evaluating the risks of material errors when auditing and exercising doubt. more effectively in order to achieve the quality of the information in the auditor’s report.